Kepadatan Nematoda Gastrointestinal Itik Manila (Cairina moschata) yang Dipasarkan di Pasar Flamboyan Kota Pontianak - Tri Rima Setyawati, Ida Zaharah, Ari Hepi Yanti (Jurnal Protobiont, 2016)
Gastrointestinal Nematode worms have serious impacts on infected birds and humans, among other causing anemia, digestive problems and decreased immunity. This research aims to find out the species and density of Nematode worms in the gastrointestinal tract of the muscovy duck (Cairina moschata) sold in Flamboyan Market Pontianak. Samples of worms were taken from January to March 2016. The number of samples observed was 90 muscovy ducks. The Nematode worms that found fixed with Formalgliserin (FG) solution.The identification was carried out in the Laboratory of Zoology at the Department of Biology, Faculty of Mathematics and Natural Sciences, Tanjungpura University Pontianak. 3 of 90 samples of muscovy duck were infected by gastrointestinal Nematodes. The research discovered two species of gastrointestinal Nematode worms i.e. Ascaridia galli and Heterakis gallinarum. A. galli had a density rate of 0.024 ind/ml and H. gallinarum at 1 ind/ml. The frequency of presence of H. gallinarum was lower (1,11%) and A. galli (2,22%).